SEP-class genes in Prunus mume and their likely role in floral organ development. Issue 1 (December 2017) - Zhou, Yuzhen; Xu, Zongda; Yong, Xue; Ahmad, Sagheer; Yang, Weiru; Cheng, Tangren; Wang, Jia; Zhang, Qixiang
Abstract Background Flower phylogenetics and genetically controlled development have been revolutionised during the last two decades. However, some of these evolutionary aspects are still debatable. MADS-box genes are known to play essential role in specifying the floral organogenesis and differentiation in numerous model plants likePetunia hybrida, Arabidopsis thaliana andAntirrhinum majus . SEPALLATA (SEP) genes, belonging to the MADS-box gene family, are members of the ABCDE and quartet models of floral organ development and play a vital role in flower development. However, few studies of the genes inPrunus mume have yet been conducted. Results In this study, we cloned fourPmSEPs and investigated their phylogenetic relationship with other species. Expression pattern analyses and yeast two-hybrid assays of these four genes indicated their involvement in the floral organogenesis withPmSEP4 specifically related to specification of the prolificated flowers inP. mume . It was observed that the flower meristem was specified byPmSEP1 andPmSEP4, the sepal byPmSEP1 andPmSEP4, petals byPmSEP2 andPmSEP3, stamens byPmSEP2 andPmSEP3 and pistils byPmSEP2 andPmSEP3 . Conclusion With the above in mind, flower development inP. mume might be due to an expression of SEP genes. Our findings can provide a foundation for further investigations of the transcriptional factors governing flower development, their molecular mechanisms and genetic basis.